Marketing Analysis of Rahn Products Through The Implementation Of Shariah Values In Increasing Customer Trust - Agatha, Talitha Hardiyan; Handayani, Anita (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This qualitative case study investigates the impact of sharia-based marketing strategies on customer trust in Rahn pawn products at Pegadaian Syariah in Gresik, Indonesia. Methodology: Employing purposive sampling, data were gathered through in-depth interviews, participant observations, and document analysis involving five staff members and eight customers. Findings and Results: Thematic analysis revealed that the application of sharia values—particularly transparency, justice, and ethical service—significantly enhances customer trust and loyalty. Transparency and continuous customer education were identified as the most influential factors, particularly among first-time users. While findings indicate a strong alignment between ethical marketing and customer confidence, the study is limited by its local scope and relatively small sample size. Novelty: Future research should explore comparative analyses across regions or institutions. Originality: This paper contributes to the growing literature on Islamic financial marketing by offering localized insights. Conclussions : underscores the need for tailored, value-based marketing strategies in enhancing engagement with Islamic pawnshop services. Type of Paper : Research Paper